Does the Chinese carbon trading policy achieve its goals？ Evidence from seven pilot provinces - Yang, Yifan. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Economics.; Advisor: Ujjayant Chakravorty.; Committee: Steve Cicala.; Keyword: Economics.